Determinants of online purchase intention and moderating role of trust in social network websites in Malaysia - Fard, Saeideh Sharifi; Tamam, Ezhar; Hassan, Md Salleh; Waheed, Moniza (IDOSI Publications, 2017)
The rapid growth of social networking sites (SNSs) has led to a change in marketing strategies and purchase behaviour of consumers. Drawing on the Extended Unified Theory of Acceptance and Use of Technology, a theoretical basis for the online buying intention based trust, performance expectancy, hedonic motivation, habit, social influence and effort expectancy constructs was examined. The data came from a sample of 370 students who had a prior experience in online buying. It was found that habit, hedonic motivation and performance expectancy were significant predictors of buying intention; however, effort expectancy and social influence did not significantly predict purchase intention. Habit had stronger influence on buying intention for customers with a high level of trust, whereas hedonic motivation and performance expectancy had a higher effect for customers with a low level of trust. Theoretical and practical implications of the findings are discussed.